DETERMINATION OF THE PROFILE OF PATIENTS WITH HEART FAILURE (HF) ON A BASIC HEALTH UNIT (UBS) OF MARINGÁ-PR (Fiep Bulletin - online, 2013)
The aim of this study was to determine the profile of patients with HF users in a UBS, Maringá-PR. We conducted a cross-sectional, population type, the UBS of Maringá, Paraná, whose data were collected from electronic medical records of patients with IC, available from the Unit on September 5, 2012. We selected 83 patients, among them 39 (46.99%) were male and 44 (53%) were female. For inclusion in the study the patient needed to use the drug digoxin or included in the medical record diagnosis of HF. For the values ??of absolute and relative frequency, we used the program in Excel 2007 that were categorized values ??for males and females. All information collected was kept confidential, as well as the personal data of all subjects who signed a consent form. For to determine the profile of UBS were collected the following parameters: the pressure level, anthropometric measurements (weight, height and body mass index), age and gender. Quantitative variables were presented as mean, standard deviation and graphs with values ??expressed in percentages and percentage of prevalence. The survey shows that 54.2% of patients (n = 45) are aged above 70 years. The average age for males and females were 69.8 ± 12.5 and 71.4 ± 13.8, respectively. While body weight was similar for both genders. Women have a lower height (1.7 ± 0.07 m for males and 1.5 ± 0.04 for females), but have BMI (body mass index) higher. However, the data indicate that there is a definite pattern for patients with HF served for the SUS (Unified Health System), as there are risk factors that affect disease progression.
Keywords: Profile of Patients; Heart Failure; Health Basic Unity